Três ensaios sobre o envelhecimento populacional e seus efeitos econômicos - Zuanazzi, Pedro Tonon (2017)
This dissertation is comprised of three essays that relate the demographic transition and the population aging to its economic impacts. The relevance of this topic in literature has increased since the second half of the last century, when studies starts to use, in addition to population growth, changes in the age structures of the population. In the case of Brazil, population will face important challenges in the coming years, such as the population decline and a continuous increase in the elderly population, thus resulting in the end of the demographic dividend - a period when there is an increase in the participation of the population aged 15-64 years in the total population. Thus, in the first essay, the main objective is to evaluate the impact of the demographic dividend on per capita GDP growth using a panel database of countries. The results show that, although the demographic dividend is directly related to the per capita GDP, its effects are partially alleviated due to its inverse relation with the proportion of workers among the population aged 15-64 years. In the second essay, we analyze the evolution of the relationship between the Brazilian's age and their probability to be a saver, measuring the effect of aging on private savings through the Household Budget Surveys (POFs) of 1995-1996, 2002-2003 and 2008-2009. The results, obtained through a multinomial logit model, indicate that demography should contribute slightly to increase the number of savers in the coming years, which indicates that the country lives a smooth second demographic bonus. Finally, considering that several social security reforms have been applied in Brazil since the Federal Constitution of 1988, necessary in part by the process of population aging, the third essay aims at estimating the impact of the modifications of one of these reforms on the Brazilians probability to save. In this case, we investigated the reform originated by Constitutional Amendments 41 and 47, which occurred between the 2002-2003 and 2008-2009 POFs and substantially affected only the civilian public employees, which allowed the use of a difference-in-differences using the other workers as a control group. The results are that the reform has impacted on an increase in the percentage of savers, in accordance with the life cycle hypothesis.